Evaluasi Kebijakan Hukum Pajak Terhadap Sektor Bisnis: Analisis Ketatanegaraan dan Urgensi Reformasi - Wilma Silalahi; Yunita Estu Lestari (Jurnal Pustaka Cendekia Pendidikan, 2025)
Taxation constitutes a primary instrument of the state in realizing fiscal sovereignty and supporting national development. Nevertheless, tax law policies directed toward the business sector often generate significant challenges, particulary in term of legal certainty, fiscal equity, and institutional effectiveness. This study aims to evaluate tax law policies affecting the business sector by examining constitutional principles-namely legality, justice, and accountability-while emphasizing the urgency of tax reform. The research employs a normative juridical method with statutory, conceptual, and comparative approaches. The findings indicate fiskal burdens. Tax reform is therefore essensial to strengthen the constitutional system, ensnure legal certainty, and balance the interests of the state and the business sector.